Ionisk selvsamling med farvestoffet hydroxynaphtol blue og tensidet benzyldimethyldodecylammonium- chlorid - Kæstel-Hansen, Jacob; Danielsen, Mia; Trojaborg, Rasmus; Pedersen, Mads (UCPH NanoScience - a student research journal, 2017)
N/A